2021
DOI: 10.5430/jct.v10n1p29
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Undergraduate and Graduate Student Research in STEM Education

Abstract: Student research in STEM education is an important learning component for both undergraduate and graduate students. It is not sufficient for students to learn passively in lecture-based classrooms without engaging and immersing themselves in the educational process through real-world research learning. Experiential learning for STEM students can involve conducting research, alongside and through the guidance of their professors, early in a student’s undergraduate or graduate program. The authors consider such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…The results of the study are encouraging for future summer programming for high school students and teachers. Previous research had found the connections between hands-on experiential learning activities and student interest and learning in STEM (Birney et al, 2021a(Birney et al, , 2021b(Birney et al, , 2022Brandt, 2016;Hoskins, 2019;Plank, 2017;Wilcox, Cruse, & Clough, 2015). Grant funding had provided the needed resources to provide both the professional experiences for teachers and learning opportunities for students.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the study are encouraging for future summer programming for high school students and teachers. Previous research had found the connections between hands-on experiential learning activities and student interest and learning in STEM (Birney et al, 2021a(Birney et al, , 2021b(Birney et al, , 2022Brandt, 2016;Hoskins, 2019;Plank, 2017;Wilcox, Cruse, & Clough, 2015). Grant funding had provided the needed resources to provide both the professional experiences for teachers and learning opportunities for students.…”
Section: Discussionmentioning
confidence: 98%
“…The research team has been conducting research on activities related to multiple NSF grants since 2017 (e.g., recent publications such as Birney et al, 2021aBirney et al, , 2021bBirney et al, , 2022, and the driving theoretical framework across this research has been based on Bandura's (1986Bandura's ( , 1997 self-efficacy and social cognitive theory in which student cognitive and social development happens through social interactions between students through collaborative work and teacher/student interactions, which has broad implications for student sense of self-efficacy. Nava and Park (2021) had indicated that real-world STEM learning through hands-on activities and field-based experiences can improve content knowledge and self-efficacy.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Lower scores represent lower levels and higher scores represent higher levels. Statistical analysis across the studies of this project was conducted using linear modeling and chi-square analysis and can be found in the previous publications (e.g., Birney et al, 2021aBirney et al, , 2021bBirney et al, , 2022.…”
Section: Methodsmentioning
confidence: 99%
“…The BOP-CCERS project and study (e.g., recent publications such as Birney et al, 2021aBirney et al, , 2021bBirney et al, , 2022 has rested on a theoretical foundation with Bandura's (1986Bandura's ( , 1997 self-efficacy and social cognitive theory in which student cognitive and social development occurs through social interactions between students and interactions with the teacher, who functions as a coach or guide for student inquiry. The BOP-CCERS project is grounded by this framework to create a community of learners and develop self-efficacy in line with Vygotsky's (1987) sociocultural theory of learning.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Furthermore, the research focus taken is almost the same as the previous research. Students are less courageous in taking different topics because they are afraid it will take them a long time to complete their studies (Birney et al, 2021;Brata, 2015).…”
Section: Introductionmentioning
confidence: 99%